Pendidikan dan Masyarakat Serta Pentingnya Pendidikan Karakter Terhadap Moralitas Pelajar di Lingkungan Masyarakat Era Digital - Hasan Basri (Yayasan Al-Ahliyah Al-Islamiyah Aek Badak, 2023)
Education is the process of teaching and learning patterns of human behavior according to what society expects. Education is concerned with the development and changes in the behavior of students. Education is closely related to the transmission or distribution of knowledge, attitudes, beliefs, skills and other aspects of behavior to the younger generation. Human behavior is essentially almost entirely social, that is, what is learned in interaction with other humans. What we learn is the result of relationships with other people at home, school, playgrounds, workplaces, and so on. The learning material or content of education is determined by the group or community. This article philosophically aims to explore the basic ideas and concepts implicit in education and society. What is education and social environment? What is education and society? What is the perspective of education in society?Community-based education is the concept of education